Workload And Staff Compliance Predict Medical Record Completion Accuracy: Beban Kerja Dan Kepatuhan Staf Memprediksi Akurasi Pengisian Rekam Medis - Jofani Dimas Perdana; Kosasih Kosasih; Ayu Laili Rahmiyati (Academia Open, 2026)
General Background Accurate clinical documentation is crucial for healthcare service quality and patient safety. Specific Background High administrative volumes often cause inconsistencies in data entry among hospital personnel. Knowledge Gap Previous studies tend to evaluate administrative burdens and procedural adherence separately rather than assessing their simultaneous interaction on documentation precision. Aims This quantitative research analyzes how administrative workloads and procedural adherence dictate data entry precision at Bintang Amin Hospital. Results An analytical survey utilizing multiple linear regression on 78 purposively sampled respondents revealed that excessive administrative workloads significantly reduce documentation precision. Conversely, strict procedural adherence significantly increases data precision. Simultaneously, these two factors account for 77.5 percent of the variance in overall documentation precision. Novelty The primary innovation lies in evaluating the simultaneous interaction of administrative pressure and standard operating procedure adherence on clinical documentation precision using Method of Successive Interval data transformation. Implications Healthcare facilities must optimize task distribution and reinforce a strict procedural adherence culture to guarantee clinical data precision and ensure patient safety. Highlights Excessive administrative tasks significantly reduce the precision of healthcare documentation. Strict adherence to standard operating procedures strongly dictates clinical data quality. Task management and disciplinary culture simultaneously govern overall information precision. Keywords Workload; Staff Compliance; Medical Records; Documentation Accuracy; Hospital Administration